Student Volunteering as a Solution for Undergraduate Health Professions Education: Lessons From the COVID-19 Pandemic - Chawłowska, Ewelina; Staszewski, Rafał; Lipiak, Agnieszka; Giernaś, Bogusz; Karasiewicz, Monika; Bazan, Dominika; Nowosadko, Maria; Cofta, Mateusz; Wysocki, Jacek (Frontiers in Public Health, 2021)
In response to the COVID-19 pandemic, many medical universities worldwide, including the Poznan University of Medical Sciences, launched student volunteering projects (SVPs). We examined our student volunteers’ perceptions on the conditions, safety, costs and benefits of their participation in the SVP. Using this information, we attempted to assess the viability of SVPs as a solution for health professions education during and after the pandemic. The main research tool was a questionnaire on students’ perceptions of their participation in the SVP. As a complementary qualitative method, we used semi-structured interviews with the volunteers. Our respondents (n=158) perceived conditions and safety generally positively: most reported having personal protective equipment (89.24%), technical support (88.61%), and induction training (79.11%). Only 38.61% said they had access to psychological support. Benefits (e.g. an opportunity to make new contacts or receiving positive reactions from patients and staff) seemed to outweigh costs. 65.82% of the respondents agreed that they learnt new interesting things. A majority noticed the development of their soft skills (social 86.08%; organisational 78.48%; stress management 68.99%), while 40.51% – the development of their medical skills. The interviews pointed to additional benefits for students such as gaining insight of the healthcare system, and costs such as distress caused by some patient interactions. We conclude that student volunteering could become a viable solution for health professions education. To maximise its educational potential, volunteers’ needs must be explored, psychological support ensured, and opportunities for mentoring and reflection provided. The organisational framework of a SVP should be culturally sensitive.